(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2026)
This article investigates how immersive audiovisual environments mediated by computational systems reconfigure the relationships between body, space, and perception in contemporary performance within the context of the expanded scene. It starts from the shift in projection mapping practices, which no longer operate merely as visual surfaces but instead constitute dynamic and responsive environments. The objective is to understand how the integration of different technologies contributes to the production of spatiality and sensory experience. To this end, the study conducts a case analysis of the performance Syn: Unfolded Horizons of Bodily Senses, created by the Rhizomatiks collective in collaboration with the ELEVENPLAY company, combined with an examination of records and documents produced by the collective itself. The research is grounded in the concepts of media performance, intermediality, and scenography as a relational system, drawing on theoretical contributions concerning digital performance, the relationship between media and theatre, and the production of spatiality in contemporary performance. The analysis discusses how the integration of body sensors, real-time processing, projection, light, and sound generates an unstable perceptual field in which the image becomes a constitutive component of spatiality and sensory experience, reorganizing the conditions of perception. As a contribution, the article proposes a critical reflection on the ornamental use of audiovisual technologies in contemporary performance.